Metformin: Activation of 5′ AMP-activated protein kinase and its emerging potential beyond anti-hyperglycemic action - Goel, Sanjay; Singh, Ravinder; Singh, Varinder; Singh, Harmanjit; Kumari, Pratima; Chopra, Hitesh; Sharma, Rohit; Nepovimova, Eugenie; Valis, Martin; Kuca, Kamil; Emran, Talha Bin (Frontiers in Genetics, 2022)
Metformin is a plant-based drug belonging to the class of biguanides and is known to treat type-2 diabetes mellitus (T2DM). The drug, combined with controlling blood glucose levels, improves the body’s response to insulin. In addition, trials have identified the cardioprotective potential of metformin in the diabetic population receiving the drug. Activation of 5′ AMP-activated protein kinase (AMPK) is the major pathway for these potential beneficial effects of metformin. Historically, much emphasis has been placed on the potential indications of metformin beyond its anti-diabetic use. This review aims to appraise other potential uses of metformin primarily mediated by the activation of AMPK. We also discuss various mechanisms, other than AMPK activation, by which metformin could produce beneficial effects for different conditions. Databases including PubMed/MEDLINE and Embase were searched for literature relevant to the review’s objective. Reports from both research and review articles were considered. We found that metformin has diverse effects on the human body systems. It has been shown to exert anti-inflammatory, antioxidant, cardioprotective, metabolic, neuroprotective, anti-cancer, and antimicrobial effects and has now even been identified as effective against SARS-CoV-2. Above all, the AMPK pathway has been recognized as responsible for metformin’s efficiency and effectiveness. Owing to its extensive potential, it has the capability to become a part of treatment regimens for diseases apart from T2DM.